Cost-effectiveness Analysis of Lorlatinib in Patients Previously Treated with Anaplastic Lymphoma Kinase Inhibitors for Non-small Cell Lung Cancer in Greece - George Gourzoulidis; Oresteia Zisimopoulou; Nadia Boubouchairopoulou; Christina Michailidi; Chrissy Lowry; Charalampos Tzanetakos; Georgia Kourlaba (Journal of Health Economics and Outcomes Research)
**Background:** Non-small cell lung cancer (NSCLC), which accounts for about 80%-85% of lungcancer cases, is a leading cause of cancer-related death worldwide. Lorlatinib is a potent third-generation anaplastic lymphoma kinase (ALK) inhibitor approved for the treatment of patients with advanced, ALK-positive NSCLC previously treated with at least one second-generation ALK tyrosine kinase inhibitor.